IMUNITAS DAN KESEHATAN TUBUH MELALUI AKTIVITAS OLAHRAGA YANG EFEKTIF - Nimrot Manalu; Ibrena Tarigan; Nurul Ikhwani; Win Sara Diwa; Zaskia Al Yasmin Saragih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of sports activities on immunity and body health. This study used a quantitative method with a survey approach. The research sample was determined using a purposive sampling technique with a total of 30 respondents who exercise at least 2–3 times a week. The results showed that the majority of respondents had a high level of sports activity (46.7%), while the majority of respondents' health conditions were in the good category (50%). The results of the Pearson Product Moment correlation test showed a correlation coefficient value of r = 0.72 with a significance value of 0.000 < 0.05. Based on the results of the study, it can be concluded that effective and regular sports activities have a positive influence on immunity and body health.